Prospective dosing of warfarin based on cytochrome P-450 2C9 genotype - Voora, Deepak; Eby, Charles; Linder, Mark W.; Milligan, Paul E.; Bukaveckas, Bonny L.; McLeod, Howard L.; Maloney, William; Clohisy, John; Burnett, Steven R.; Grosso, Leonard; Gatchel, Susan K.; Gage, Brian F. (Thrombosis and Haemostasis, 2005)
Cytochrome P-450 2C9 (CYP2C9) polymorphisms (CYP2C9*2 and CYP2C9*3) reduce the clearance of warfarin, increase the risk of bleeding, and prolong the time to stable dosing. Whether prospective use of a retrospectively developed algorithm that incorporates CYP2C9 genotype and nongenetic factors can ameliorate the propensity to bleeding and delay in achieving a stable warfarin dose is unknown. We initiated warfarin therapy in 48 orthopedic patients tailored to the following variables: CYP2C9 genotype, age, weight, height, gender, race, and use of simvastatin or amiodarone. By using pharmacogenetics-based dosing, patients with a CYP2C9 variant achieved a stable, therapeutic warfarin dose without excessive delay. However compared to those without a CYP2C9 variant, patients with a variant continued to be at increased risk (hazard ratio 3.6, 95% confidence interval 1.4–9.5, p = 0.01) for an adverse outcome (principally INR > 4), despite pharmacogenetics-based dosing. There was a linear relationship (R2 = 0.42, p < 0.001) between the pharmacogenetics-predicted warfarin doses and the warfarin maintenance doses, prospectively validating the dosing algorithm. Prospective, perioperative pharmacogenetics-based dosing of warfarin is feasible; however, further evaluation in a randomized, controlled study is recommended.
Keywords: Polymorphism; prospective studies; cytochrome P-450 enzyme system/genetics; warfarin/administration and dosage